Analýza možností prodeje webových her - Križek, Petr; Križek Petr (České vysoké učení technické v Praze, 2015)
Cílem práce je určit vhodný obchodní model pro malé nebo neznámé vývojáře a zodpovědět otázku, zda bude daný model v konkrétním případě ziskový. Teoretická část pojednává o rozdělení webových her do kategorií podle technologií, dále je věnována pozornost jednotlivým obchodním modelům a jejich srovnání. Praktická část práce se zabývá analýzou zákazníka a konkurence a projektem vlastní hry. Jako obchodní model byl vybrán model mikrotransakcí a investice do projektu byla hodnocena kladně.

The goal of the thesis is to determine suitable business model for small or unknown developers and to answer the question whether the model would be profitable in particular case. The theoretical part of the thesis deals with categorization of web games according to the used technologies. The work also includes the analysis of business models and their comparison. In practical part the analysis of the customer and the competitor were conducted. The rest of the thesis includes author's game project and evaluation of investment's profitability of the project. The microtransaction (free-to-play) model was chosen as business model and the result of evaluation was positive.
Analysis of sales opportunities web games
Keywords: Webová hra, online hra, obchodní model, byznys model, analýza zákazníka, analýza konkurence, ekonomická efektivnost